Sex Differences in the Development of the Rodent Corticolimbic System - Premachandran, Hanista; Zhao, Mudi; Arruda-Carvalho, Maithe (Frontiers in Neuroscience, 2020)
In recent years, a growing body of research has shown sex differences in the prevalence and symptomatology of psychopathologies such as depression, anxiety, and fear-related disorders, all of which show high incidence rates in early life. This has highlighted the importance of including female subjects in animal studies, as well as delineating sex differences in neural processing across development. Of particular interest is the corticolimbic system, comprising the hippocampus, amygdala, and medial prefrontal cortex. In rodents, these corticolimbic regions undergo dynamic changes in early life, and disruption to their normative development is believed to underlie the age and sex-dependent effects of stress on affective processing. In this review, we consolidate research on sex differences in the hippocampus, amygdala, and medial prefrontal cortex across early development. First, we briefly introduce current principles on sexual differentiation of the rodent brain. We then showcase corticolimbic regional sex differences in volume, morphology, synaptic organization, cell proliferation, microglia, and GABAergic signalling, and explain how these differences are influenced by perinatal and pubertal gonadal hormones. In compiling this research, we outline evidence of what and when sex differences emerge in the developing corticolimbic system, and illustrate how temporal dynamics of its maturational trajectory may differ in male and female rodents. This will help provide insight into potential neural mechanisms underlying sex-specific critical windows for stress susceptibility and behavioral emergence.